A Phase 2a Multicenter, Double‐Blind, Placebo‐Controlled, Crossover Trial to Investigate the Efficacy, Safety, and Toleration of CP‐866, 087 (a High‐Affinity Mu‐Opioid Receptor Antagonist) in Premenopausal Women Diagnosed with Female Sexual Arousal Disorder (FSAD). (24th January 2013) - Orri, Miguel; Abraham, Lucy; Giraldi, Annamaria
Abstract Introduction Female sexual arousal disorder (FSAD) is a condition that can affect women of all ages and have a significant negative impact on emotional well‐being. Aims The aim of this study is to prospectively evaluate the effects of CP‐866, 087, a selective mu‐opioid receptor antagonist, in premenopausal women with FSAD. Methods The study included 51 women (20–45 years of age) with FSAD. All women received placebo and two of three planned doses of CP‐866, 087 (1, 3, and 10 mg) for 6 weeks in each of three double‐blind treatment periods. Efficacy was determined through a series of measures to assess sexual functioning, sexual activity, sexual distress, and perceived meaningful benefit as a result of treatment. In addition, a semi‐structured exit interview was conducted at the end of the fourth treatment period or withdrawal to provide a more in‐depth, qualitative description of the participants' symptoms, response to treatment, and treatment satisfaction to augment the quantitative assessments. Main Outcome Measures The within‐subject differences from placebo in the change from baseline were compared across a range of measures of sexual function. Summary statistics and 90% confidence intervals were calculated. A qualitative analysis of the exit interview was conducted based on grounded theory methods. Results Although improvements were seen with CP‐866, 087 in the key efficacy end points, there was no clinical treatment benefit over placebo. The exit interview analysis suggested that being part of the study and taking positive action to search for a solution to the women's sexual disorder may have been a significant factor in the behavioral changes that were seen, as opposed to the drug treatment itself. Conclusions Discerning the potential benefit of pharmacotherapy in a heterogeneous condition such as FSAD is challenging. Participation in a clinical trial combined with a commitment to actively engage in sexual activity may in itself create an environment that is conducive to symptom improvement. Orri M, Abraham L, and Giraldi A. A phase 2a multicenter, double‐blind, placebo‐controlled, crossover trial to investigate the efficacy, safety, and toleration of CP‐866, 087 (a high‐affinity mu‐opioid receptor antagonist) in premenopausal women diagnosed with female sexual arousal disorder (FSAD). J Sex Med 2013;10:2484–2496.